Design and synthesis of phthalazine-based compounds as potent anticancer agents with potential antiangiogenic activity via VEGFR-2 inhibition - Salwa Elmeligie; Asmaa M. Aboul-Magd; Deena S. Lasheen; Tamer M. Ibrahim; Tamer M. Abdelghany; Sohair M. Khojah; Khaled A. M. Abouzid (Journal of Enzyme Inhibition and Medicinal Chemistry, 2019)
In the designed compounds, either a biarylamide or biarylurea moiety or an N-substituted piperazine motif was linked to position 1 of the phthalazine core. The anti-proliferative activity of the synthesised compounds revealed that eight compounds (6b, 6e, 7b, 13a, 13c, 16a, 16d and 17a) exhibited excellent broad spectrum cytotoxic activity in NCI 5-log dose assays against the full 60 cell panel with GI50 values ranging from 0.15 to 8.41 µM. Moreover, the enzymatic assessment of the synthesised compounds against VEGFR-2 tyrosine kinase showed the significant inhibitory activities of the biarylureas (12b, 12c and 13c) with IC50s of 4.4, 2.7 and 2.5 μM, respectively, and with 79.83, 72.58 and 71.6% inhibition of HUVEC at 10 μM, respectively. Additionally, compounds (7b, 13c and 16a) were found to induce cell cycle arrest at S phase boundary. Compound 7b triggered a concurrent increase in cleaved caspase-3 expression level, indicating the apoptotic-induced cell death.